SUNSPACE, A Porous Material to Reduce Air Particulate Matter (PM) - Zanoletti, Alessandra; Bilo, Fabjola; Borgese, Laura; Depero, Laura E.; Fahimi, Ario; Ponti, Jessica; Valsesia, Andrea; La Spina, Rita; Montini, Tiziano; Bontempi, Elza (Frontiers in Chemistry, 2018)
The World Health Organization reports that every year several million people die prematurely due to air pollution. Poor air quality is a by-product of unsustainable policies in transportation, energy, industry, and waste management in the world's most crowded cities. Particulate matter (PM) is one of the major element of polluted air. PM can be composed by organic and inorganic species. In particular, heavy metals present in PM include, lead (Pb), mercury (Hg), cadmium, (Cd), zinc (Zn), nickel (Ni), arsenic (As), and molybdenum (Mo). Currently, vegetation is the only existing sustainable method to reduce anthropogenic PM concentrations in urban environments. In particular, the PM-retention ability of vegetation depends on the surface properties, related to the plant species, leaf and branch density, and leaf micromorphology. In this work, a new hybrid material called SUNSPACE (SUstaiNable materials Synthesized from by-Products and Alginates for Clean air and better Environment) is proposed for air PM entrapment. Candle burning tests are performed to compare SUNSPACE with Hedera Helix L. leafs with respect to their efficacy of reducing coarse and fine PM. The temporal variation of PM10 and PM2.5 in presence of the trapping materials, shows that Hedera Helix L. surface saturates more rapidly. In addition, the capability of SUNSPACE in ultrafine PM trapping is also demonstrated by using titanium dioxide nanoparticles with 25 nm diameter. Scanning electron microscope (SEM) and Transmission electron microscope (TEM) images of SUNSPACE after entrapment tests highlight the presence of collected nanoparticles until to about 0.04 mm in depth from the sample surface. N2 physisorption measurements allow to demonstrate the possibility to SUNSPACE regeneration by washing.